Improving the Quality of Dasawisma Administration through Collaboration with Universities - Nurmala Sari; Ernita Puspa Dewi; Hannisa Fitri Effendi; Ramadhan Fathur Rahman Syah; Ziada Filosofia (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
The low quality of Dasawisma administrative management remains a major challenge in supporting the effectiveness of the Family Empowerment and Welfare (PKK) programs at the community level. This problem is characterized by poorly organized family data records, weak documentation of activities, and limited understanding among administrators regarding the strategic role of administration as a basis for planning and decision-making. This Community Service Program (PKM) aims to improve the quality of Dasawisma administration through collaboration between higher education institutions and Dasawisma groups as an effort to strengthen community organizational governance. The method employed is a participatory community organizing approach, encompassing stages of joint planning, technical administrative assistance, training, and reflective evaluation. The results indicate an improvement in administrators' understanding and skills in managing administrative tasks, the establishment of more systematic data and activity recording systems, and increased participation and organizational ownership among Dasawisma members. Furthermore, the program encouraged the emergence of local leadership and collective awareness of the importance of as an instrument for institutional strengthening. Overall, collaboration with higher education institutions proved effective in promoting sustainable improvements in Dasawisma administrative governance.